From the Declaration to the accurate Recognition of Minority Rights: World Experience and Realities in Post-Soviet Countries - Yevheniia Levcheniuk; Fedir Vlasenko; Dmytro Tovmash (International Society of Philosophy and Cosmology, 2021)
The article deals with different approaches to sexual minorities, both of legislative nature and of their public perception in different world countries. Enshrining equal human rights and freedoms inlaws is a sign of society's democratisation and the level of civil society's maturity. Therefore, educating people about the tolerant attitude towards representatives of different sexual orientation is an important task for post-Soviet countries, including Ukraine. Based on Western Europe and the USA's experience, mechanisms for protecting the minority rights in post-Soviet countries are distinguished, which requires the adoption of appropriate laws and society's tolerant attitude.